Analysis of Consistency in Students' Understanding of Multi-Representations in the Context of Determining One-Dimensional Kinematics Distance - Ahmad Ridlotul Adha; Muhammad Reyza Arief Taqwa (Universitas Lambung Mangkurat, 2024)
A structured and comprehensive understanding of physics concepts is crucial to physics learning. Such proficiency is characterized by the consistency in students' thought processes across multiple representations. This research aims to ascertain the consistency in the thought processes of first-year students when determining distance in multiple representations. This study employed a descriptive research design with a quantitative-qualitative approach, involving 77 students as research subjects. The participants are divided into classes: Class H with 41 students and Class I with 36 students. Data analysis techniques included quantitative descriptive analysis and Huberman and Miles' analysis. The research instrument consisted of 28 reasoned multiple-choice items that have undergone validation. The findings indicate that only 8 (10.39%) students possess a precise and consistent understanding of the definition of distance, applying it across various representations. A small proportion (12.99%) experiences misconceptions. These research findings corroborate previous studies, emphasizing that, in general, first-year students are novices in physics.